2017
DOI: 10.1002/advs.201700520
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence‐Assisted Understanding of Nature‐Inspired Superhydrophobic Behavior

Abstract: In recent years, state‐of‐the‐art computational modeling of physical and chemical systems has shown itself to be an invaluable resource in the prediction of the properties and behavior of functional materials. However, construction of a useful computational model for novel systems in both academic and industrial contexts often requires a great depth of physicochemical theory and/or a wealth of empirical data, and a shortage in the availability of either frustrates the modeling process. In this work, computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The adhesive forces between mud droplet (droplet size 5 μL) and SiO2@PDMS/APP/PER-coated samples were also measured using a high-sensitivity micro electromechanical balance system that was reported in our previous work. [18] However, this -OH band was notably weakened in the SiO2@PDMS/APP/PER-coated cotton fabric, compared with the untreated articles and it is observed that new peaks appeared around 1261, 860, 798 cm -1 (Figure 1b), which correspond to the P-O-P, P=O (from APP) and Si-C stretches from SiO2/PDMS, respectively. [5,19] The FT-IR spectra show that the obtained surfaces were efficiently covered with APP, SiO2 and PDMS.…”
Section: Earth Repellent Testsmentioning
confidence: 95%
“…The adhesive forces between mud droplet (droplet size 5 μL) and SiO2@PDMS/APP/PER-coated samples were also measured using a high-sensitivity micro electromechanical balance system that was reported in our previous work. [18] However, this -OH band was notably weakened in the SiO2@PDMS/APP/PER-coated cotton fabric, compared with the untreated articles and it is observed that new peaks appeared around 1261, 860, 798 cm -1 (Figure 1b), which correspond to the P-O-P, P=O (from APP) and Si-C stretches from SiO2/PDMS, respectively. [5,19] The FT-IR spectra show that the obtained surfaces were efficiently covered with APP, SiO2 and PDMS.…”
Section: Earth Repellent Testsmentioning
confidence: 95%
“…Then, WCA, SA, advancing/receding contact angle, adhesive force, and integrity of microtopography should all be taken into evaluation systems. 69 The best solution is to develop a highly integrated testing system which can test all-around surface wettability. With the aid of an external humidity/temperature control system, gas circuit system, and super-high-speed camera, liquid volatilization and icing processes can be studied via this integrated system in different atmospheres or in vacuum.…”
Section: Current Developments and Challenges Of Designs Of Superhydromentioning
confidence: 99%
“…In recent times, machine learningbased nano-coatings are in the rise, DOI: 10.30726/esij/v8.i4.2021.84026 owing to their ability to make experimentation easier. Machine learning models can be used to characterise surface attributes such as adhesion forces, water contact and sliding angles, and features of the morphology that determine how water droplets bounce over a surface during self-cleaning [24]. The researchers also established some specific goals for themselves, stating that a self-cleaning surface's water contact angle must be more than 150 degrees.…”
Section: Machine Learning Models For Tuning the Nanomaterialsmentioning
confidence: 99%